Effects of Cold Rolling and Aging Treatment on the Properties of Cu-Be Alloy - Mohamed, M. I. (Engineering, Technology & Applied Science Research, 2019)
The effects of precipitated phases during aging treatment on the properties of the Cu-Be alloy have been extensively studied. In this study, the effect of cold rolling on the precipitated phases of the Cu-Be alloy compared with non-deformed alloy during isothermal and low heating rate aging of 20C/min have been investigated. Hardness changes, differential scanning calorimetry (DSC), dilatation analysis, and transmission electron microscopy (TEM) were used in this study. Hardening and contraction were strongly increased at an early aging time for the cold rolled Cu-Be alloy. In addition, the DSC curves revealed an exothermic peak from the γ΄΄ phase. This peak increased and shifted to lower aging time by increasing the cold rolling reduction. In addition, the hardness remarkably increased at lower aging temperatures for the cold rolled specimens. The contraction from the dilatation curves and the exothermic peaks shifted to lower aging temperatures in cold rolled specimens. The hardening of Cu-Be alloy is believed to be from the γ΄ phase, and the contraction and the first exothermic peak in DSC curves from γ΄΄ phase. TEM observations are in a good agreement with the above explanation and strongly revealed that γ΄΄ and γ΄ phases were highly accelerated by the effect of cold rolling